VERBS IN ENGLISH AND TOBA BATAK LANGUAGE - Melyna Christiani; Amrin Saragih (State University of Medan, 2012)
ABSTRACT The objectives of this study is restricted to investigating and describing similarities and differences of the two languages about verbs in English and Toba Batak Language, included in terms of types, functions, and forms. This study was applied by descriptive qualitative design. The data was taken an observe about Toba Batak language from some of informant and text book. The findings describied that there were some similarities and differences verbs in English and Toba Batak Language. Both the languages, the similarities describied the functions of verb has as predicates, noun phrase modifiers, adjective phrase complements, subjects, suject complements and using to be as verbs. The analysis also shown the differences as how the pattern verbs using tenses in both of the languages, the verbs using affixes. In conclusion, there are similarities and differences of verbs in English and Toba Batak Language.